Impact of private and public initiatives on individuals' employment and income during the~COVID-19 pandemic: Evidence~from Peru - Samuel Arturo Mongrut; Vivian Cruz; Daniela Pacussich (Journal of Economics, Finance and Administrative Science, 2024)
Purpose - The Purpose - of this paper is to determine the impact of private and public initiatives (financial literacy, entrepreneurship, remote work and government aid) on individual job loss and decrease in income during the COVID-19 pandemic in Peru. Design/methodology/approach The authors used an unbalanced panel data analysis with the National Household Survey for 2019-2020. The hypotheses are tested with a probit panel data model since the dependent variables are binary. Findings The study findings indicate that financial preparedness reduced the probability of having a decrease in income, but only to informal workers in metropolitan Lima. Furthermore, entrepreneurship helped mainly female informal workers to reduce their probability of becoming unemployed in metropolitan Lima. Besides, the implementation of remote work as a substitute of face-to-face work was not enough to avoid the decrease in income in the case of informal workers and it was only effective to avoid unemployment in the case of formal workers in metropolitan Lima. Finally, public aid proved to be instrumental in mitigating the decrease in income, but only to informal workers in Metropolitan Lima. Research limitations/implications The study results only apply for the first year of the pandemic. Practical implications Policymakers should focus on increasing the financial preparedness of informal workers, especially in provinces. Social implications Policymakers must expand unemployment benefits, and design public aid programs targeting informal workers in provinces. Originality/value This is the first study that analyses the impact of private and public initiatives on the decrease in income and unemployment situation of Peruvian individuals during the outbreak of the COVID-19 pandemic.
Keywords: D31; I12; I38; J64; 330; Pandemic; Personal income; Public policy; Unemployment